5d+3(d-5)=

Simple and best practice solution for 5d+3(d-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5d+3(d-5)= equation:


Simplifying
5d + 3(d + -5) = 0

Reorder the terms:
5d + 3(-5 + d) = 0
5d + (-5 * 3 + d * 3) = 0
5d + (-15 + 3d) = 0

Reorder the terms:
-15 + 5d + 3d = 0

Combine like terms: 5d + 3d = 8d
-15 + 8d = 0

Solving
-15 + 8d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 8d = 0 + 15

Combine like terms: -15 + 15 = 0
0 + 8d = 0 + 15
8d = 0 + 15

Combine like terms: 0 + 15 = 15
8d = 15

Divide each side by '8'.
d = 1.875

Simplifying
d = 1.875

See similar equations:

| (2+6i)+(3-7i)= | | -5x+40=6-3x | | x-(-20.78)=-23.49 | | g=-1/2(4)+1 | | 5x+40+5x=180 | | 15-6t/12=3/4 | | 6(2m+n-4)= | | 33.2+x+23.3+x=191.7 | | 10m-6+2m+13= | | x^2-100x+1250=0 | | f=7(0)-6 | | x+17=-14 | | (5-2i)-(3-7i)= | | -7(3n+6)=105 | | f=7(1)-6 | | 6p+4-3p= | | 11n-8-10y-7=3 | | f=7(-2)-6 | | 4=5d-16 | | -6a+5=23 | | 13.9=x/6+12.5 | | a-5/2=3a/4+a-25/6 | | v+30=84 | | 3z/2-1=-16 | | 2-14=12y+9-11y | | 7p+6+2p= | | -5/6n+8=-32 | | .25+x=-.583 | | .5m-7=-4 | | x^4+3x^3-4x^2-12=0 | | -5u+15=7(u-3) | | 2x-18=5(x+3) |

Equations solver categories